Combined transcriptome and metabolome analysis revealed the molecular mechanisms of fruit skin coloration in pink strawberry - Xiao, Wenfei; Liu, Aichun; Lai, Wenguo; Wang, Jianrong; Li, Xiaoyuan; Zha, Yan; Zhao, Bo; Chen, Xiaoyang; Yu, Hong (Frontiers in Plant Science, 2024)
Elucidating the key genes and metabolites responsible for fruit skin color is essential for the breeding of strawberry varieties with beautiful fruit color. Here, transcriptome and metabolome analyses were used to identify the key genes and metabolites associated with fruit skin color in strawberry accessions of red skin (Kaorino), white skin (2012-W02), and the pink skin (Fenyu NO.1, the F1 hybrid of Kaorino and 2012-W02). The metabolomic data showed that the content of anthocyaninrelated metabolites, such as p-Coumaroyl quinic acid, 5-Hydroxyconiferyl alcohol and Coumestrol were significantly higher in red-skinned strawberry line Kaorino than in the white-skinned line 2012-W02. The flavonoids and isoflavonoids such as syringetin and 2,7,4'-trihydroxy-isoflavone, were less expressed in the Kaorino than in the other two accessions. Transcriptome analysis revealed that the expression of genes involved in anthocyanin biosynthesis, such as BZ1, F3H, CHS, CHI, DFR, 4CL, PAL, CCR, 4CL, F5H, REF1 and UGT72E, were also significantly upregulated in the redskinned line Kaorino compared to the white-skinned line 2012-W02, while the HCT, CYP75B1, FG3, HIDH, IF7MAT, I2'H, and VR was downregulated in Kaorino. Combined transcriptome and metabolome analyses revealed that the pathways of isoflavonoid biosynthesis and flavone and flavonol biosynthesis, and the phenylpropanoid biosynthesis pathway essential for anthocyanin synthesis were commonly enriched by DRMs and DEGs. In addition, the metabolites of peonidin 3-O-glucoside, 2'-hydroxydaidzein and daidzin, and the genes of CYP93B2_16 and UGT73C6 were detected and most accumulated in pink-skinned Fenyu NO.1. This result suggested that the main strategy for obtaining a red skin color is to enhance the upstream pathway of anthocyanin biosynthesis, including the phenylpropanoid biosynthesis pathway, and to restrict the downstream steps in the flavonoid biosynthesis pathway, such as the branch pathway of flavone and flavonol biosynthesis and isoflavonoid biosynthesis.